Performance Of Mentik Wangi Rice Generation M1 From The Results Of Gamma Ray Irradiation - Ahmad Yunus; Sri Hartati; Raden Dirgori Kuneng Brojokusumo (Universitas Sebelas Maret, 2017)
Mentik wangi is one of the local rice varieties in Indonesia less attractive to farmers. That is because the rice Mentik wangi has some weakness, namely a long harvest time, easy to collapse, and the results less than the maximum productivity. To increase the interest of farmers in rice cultivation Mentik wangi, then an attempt is made to improve the quality of rice Mentik wangi properties with plant breeding techniques one of which is a genetic mutation using gamma radiation. This study was conducted to determine the performance (performance) of rice Mentik wangi (M1) results of gamma-ray radiation that is expected to have a positive properties of new or better than its origin. This research was conducted in paddy fields in the village of Nangsri Lor, District Kebakkramat, Karanganyar and implemented in September 2015 to January 2016. Data were analyzed by descriptive with sorting and comparing each individual plant at each radiation dose to the average control accurately and objective. The results showed that gained some plants that could potentially be a mutant plant that has better properties (positive) that appears at the variable plants from each individual plant, ie the number of lines T16 with a radiation dose of 300 gray tall plants are very short 86 cm, strain number T204 with a radiation dose of 200 gray pick the highest panicle length of 33.5 cm, strain number T133 with a radiation dose of 100 gray has a total number of tillers and productive tiller high of 17 rods (total) and 11 rods (productive), strain number T133 with radiation dose of 200 gray had the highest number of filled grain and 624 grain strain T70 numbers with a radiation dose of 100 gray had the highest percentage of filled grain at 96%, and the number of lines T (1-7) with a radiation dose of 100 gray and strain number T ( 1-9) with a radiation dose of 200 gray had a shorter harvesting time is 110 days.